Safe implementation of transoral incisionless fundoplication as a new technique in a tertiary care center - Shivanand Bomman; Sofya Malashanka; Adil Ghafoor; David J. Sanders; Shayan Irani; Richard A. Kozarek; Andrew Ross; Michal Hubka; Rajesh Krishnamoorthi (Korean Society of Gastrointestinal Endoscopy, 2022)
Background/Aims Transoral incisionless fundoplication (TIF) is an accepted anatomic treatment for gastroesophageal reflux disease in selected patients. In this report, we analyze our institution's programmatic allocation of resources during the safe implementation of TIF as a new procedure. Methods A retrospective analysis of all patients who underwent TIF from January 2020 to February 2021 at our institution was performed. The process of initially allocating the operating room (OR) with overnight admission and postoperative esophagram for added safety, and subsequently transitioning TIF to the endoscopy suite (ES) as an outpatient procedure was described. Patient safety and outcomes were evaluated during transition. Results Thirty patients who underwent TIF were identified. The mean age was 51.2±16.0 years. TIF was performed in an OR in nine patients (30%) and 21 (70%) in the ES. All the OR patients were admitted overnight and had routine esophagogram. In contrast, four (19%) from the ES group required clinically-indicated admission and three (14.2%) required esophagram. The mean procedure duration was significantly lower in the ES group (65.7 min vs. 84 min, p=0.02). Conclusions A stepwise, resource-efficient process was described that allowed safe initiation of TIF as a new technique and its effective transition to a fully outpatient procedure.